Natural products' antiangiogenic roles in gynecological cancer - Shangmei Jia; Ling Li; Chenghao Yu; Fu Peng (Frontiers Media S.A., 2024)
Gynecological cancers pose a significant threat to women's health. Although the pathogenesis of gynecological cancer remains incompletely understood, angiogenesis is widely acknowledged as a fundamental pathological mechanism driving tumor cell growth, invasion, and metastasis. Targeting angiogenesis through natural products has emerged as a crucial strategy for treating gynecological cancer. In this review, we conducted comprehensive searches in PubMed, Embase, Web of Science, Science Direct, and CNKI databases from the first publication until May 2023 to identify natural products that target angiogenesis in gynecologic tumors. Our findings revealed 63 natural products with anti-angiogenic activity against gynecological cancer. These results underscore the significance of these natural products in augmenting their anticancer effects by modulating other factors within the tumor microenvironment via their impact on angiogenesis. This article focuses on exploring the potential of natural products in targeting blood vessels within gynecological cancer to provide novel research perspectives for targeted vascular therapy while laying a solid theoretical foundation for new drug development.